Between Battle and Everyday Life: Female Participants of the Partisan Movement of the Smolensk Region in Ego Documents of the 1940s. - Ksenia Sak (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. In the extreme conditions of occupation, several thousand women of the Smolensk region took part in the Resistance movement. The experience of their joining partisan detachments, adaptation, and participation in the “nationwide struggle” is an integral part of the problem of the functioning of society in war conditions. Methods and materials. The boundaries of women’s possibilities in the partisan movement are considered based on ego-documents: transcripts of 1943 conversations of the Mintz Commission and memoirs of 1947. Prosopographical methods are used. Analysis and results. Social practices of women in the partisan movement of the Smolensk region were carried out within the boundaries between traditional household responsibilities and masculine combat activity. The patriarchal structure of closed partisan communities was expressed in the distribution of responsibilities, attitude to weapons, and sexual relations. Most women in the detachments were bearers of traditional values and did not oppose discrimination by the command. The most active female partisans could prove themselves in the “male territory” – in reconnaissance and combat operations. Their weapons skills placed them on a higher level of the internal social hierarchy in the unit. Female partisans highly valued their contribution to the Resistance, regardless of specific practices. Male partisans had ambiguous attitudes towards their “combat girlfriends.” Their texts mention female fighters, scouts, and nurses less often, and, occasionally, those who were engaged in housework. With limited access to weapons and unofficial obstacles to combat service, women received awards less often than men. The closed societies of partisan units retained features of the pre-war social order, significantly transformed by the extreme conditions of the occupation. The range of social practices of female partisans included both patriarchal roles and practices free from gender inequality.